Peran Mediasi Self-Efficacy dan Peran Moderator Knowledge Sharing pada Empowering Leadership dan Perceived Organizational Support terhadap Employee Performance di UKM Batik HM. Sholeh Tuban - Ahmad Nuruddin; Ahmad Rizki Sridadi (Jurnal Maksipreneur, 2019)
This study uses objects in one of the Batik industries in Tuban, which is currently experiencing a fairly rapid growth in the increasingly competitive business environment. The focus of this research is on employee performance. This study aims to investigate the mechanism between empowering leadership and perceived organiza-tional support for employee performance by using self efficacy as mediation and knowledge sharing as a moderator. This quantitative study is based on data collected using questionnaires distributed to 40 respondents of UKM Batik HM. Sholeh emplo-yees and using partial least square (PLS) technique for data analysis. In the results of the analysis using PLS, it was found that self-efficacy mediates the relationship of empowering leadership and perceived organizational support for employee perfor-mance. In addition, the role of knowledge sharing moderates or strengthens the relationship between self-efficacy and employee performance. Training of need analysis is necessary according to the more dynamic movement of the business world, especially in the batik industry. It is a rapidly growing industry, both from competitors and the technology used. So in this case, an innovation is also necessary to be able to compete effectively and to fill consumers’ needs.